Experiential Marketing’s effect on Customer Loyalty with Customer Satisfaction as Intervening Variabel - Riyanto, Kuwat; Nurelisah, Siti Hazar; Purwanti, Purwanti (Review: Journal of Multidisciplinary in Social Sciences, 2024)
This study aims to analiyze the effect of experiential marketing on customer loyalty with customer satisfaction as an intervening variabel among MS Glow customers in Cikarang. The research adopts an associative approach with 91 respondents selected through purposive sampling. Data were analyze using the SmartPls method. The results show that experiential marketing positively influences customer satisfaction, which subsequently impacts customer loyalty. Furthermore, cutomer satisfaction significantly mediates the relationship between experiential marketing and customer loyalty. This study underscores the importance of effective experiential marketing strategies to enhance customer loyalty by improving customer satisfaction.